"Harry - yer a wizard" Exploring J.K. Rowling's Harry Potter Universe - Gymnich, Marion; Birk, Hanne; Burkhard, Denise (Tectum Wissenschaftsverlag, 2017)
J. K. Rowling's " Harry Potter" series (1997-2007) has turned into a global phenomenon and her Potterverse is still expanding. The contributions in this volume provide a range of inter- and transdisciplinary approaches to various dimensions of this multifacetted universe. The introductory article focuses on different forms of world building in the novels, the translations, the film series and the fandom. Part I examines various potential sources for Rowling's series in folklore, the Arthurian legend and Gothic literature. Further articles focus on parallels between the "Harry Potter" series and Celtic Druidism, the impact Victorian notions of gender roles have had on the representation of the Gaunt family, the reception of (medieval and Early Modern) history in the series and the influence of Christian concepts on the world view expressed in the novels.